Arduino electronics blueprints: make common electronic devices interact with an Arduino board to build amazing out-of-the-box projects - Wilcher, Don (Community experience distilled, 2015)
Arduino is an open source electronics prototyping platform for building a multitude of smart devices and gadgets. Developers can benefit from using Arduino in their projects because of the ease of coding, allowing you to build cool and amazing devices supported by numerous hardware resources such as shields in no time at all. Whether you're a seasoned developer or brand new to Arduino, this book will provide you with the knowledge and skill to build amazing smart electronic devices and gadgets. First, you will learn how to build a sound effects generator using recorded audio-wave files you've made or obtained from the Internet. Next, you will build DC motor controllers operated by a web page, a slide switch, or a touch sensor. Finally, the book will explain how to build an electronic operating status display for an FM radio circuit using Arduino.